The impact of game competitive sports on some physical variables, functional, and psychological for middle school students aged (13-14) years - Abed Al- Janabi, Saad Abbas; Amir Finjan, Raad Abdul; Hassan Fleih, Zainab (International Journal of Psychosocial Rehabilitation, 2019)
Sports has witnessed a remarkable development and this development was not the result of coincidence, but relied on the use of modern foundations in training and diversity in the use of teaching methods and learning methods because of their importance in developing the level of performance of learners and stimulate their motivations and cognitive, physical and skill needs.